'An insufferable burden on businesses?' On changing attitudes to maternity leave and economic-related issues in the Times and Daily Mail. (December 2018) - Gomez-Jimenez, Eva M.
Graphical abstract: Highlights: There is change in the discourse of maternity leave in the right-of-centre UK press between 1971–1977 and 1997–2001. The Times and the Daily Mail overused economic terms when discussing maternity leave from 1997 to 2001. Improvements in maternity leave rights were unquestioned from 1971 to 1977, but presented as unaffordable from 1997 to 2001. The Times and Daily Mail showed resistance to improvements in maternity leave rights from 1997 to 2001. Abstract: This paper analyses the ways in which maternity leave has been reported, within the broader context of economic inequality, in the periods from 1971 to 1977 and from 1997 to 2001, in the right-of-centre British national press. The aim is to answer the following research questions: Has the representation of maternity leave changed in the right-of-centre UK press with the adoption of new policies, particularly in relation to economic matters? If so, in what ways? Discussions of maternity leave in newspapers are identified by uses of the phrase maternity leave . Selected findings are presented from a corpus compiled for this study of news stories (641, 996 words) in the Times and the Daily Mail, in the years in which maternity leave policies were changed in the UK (1973, 1975, 1999) plus two years before and after. Combining qualitative with quantitative methods, the analysis shows that maternity leave becomes monetized in the later period, from 1997 to 2001. The economic term that undergoes the most noticeable shift in frequency of use is afford, which is used five-times more frequently in the 1997–2001 period. A close reading of all those stories containing the term afford reveals considerable opposition in these newspapers to the introduction of new entitlements for women with new-borns, a hostility that was not apparent when improvements to maternity leave provisions were first introduced in the 1970s. This paper addresses the representation of maternity leave in the belief that this system benefit (like any other state-backed benefit in the UK system) helps in mitigating wealth inequality. It is part of a larger study exploring changes in the way in which British newspapers have represented wealth inequality in the UK from 1971 to the present.